A kormányhivatalok (a Somogy Megyei Kormányhivatal) helye és szerepe a magyar közigazgatás fejlődéstörténetében - H. Varga, Katalin; Neszményi, Zsolt (Acta Scientiarum Socialium, 2013)
The role of Government Offices (the Government Office of Somogy County) in the developmental history of the Hungarian public administration The formation of Public Administration in Hungary and the country’s historical development are interconnected. Stephen I. was the founder of the Hungarian state. He set up the county system of the kingdom, grounded the church and organised the royal council. After the Turkish occupation a significant development started in Public Administration during the reign of Maria Theresa and Joseph II. The Austro-Hungarian Compromise of 1867 gave several autonomous scopes to Hungary and it also had an effect on the structure of the Public Administration system. The Monarchy fell apart after WW 1. and the newborn countries organised their on Public Administration systems. In the Inter-War Period (1919-1939) it was â€˜hyper central’, however the central, ministerial authorities did not have any decision making power. During the Socialist era the Theory of State and Theory of Law vindicated the principle of the authority’s unity. After 1989 State and Public Administration renewed. The first democratically elected government were open towards the Western systems and founded the general institutions of the legal state. Capital and County Government Offices were set into action as a next step in the standardized regional polity in January 2011. The tasks of the Government Offices: execute the governmental tasks in the region. Their aim is to standardise regional polity. 17 decentralised polity bodies inte-grated into capital and county government offices 1st January 2011 as a result of the 288/2010. (XII. 21.) Government Order. The Government hopes more standard operation, the elimination of parallel operations, and therefore the decrease of costs as an effect of integration. Recent results have shown that several procedures can be managed easier especially the important investments or the authority procedures.